Association between genetic variants in the tumour necrosis factor/lymphotoxin α/lymphotoxin β locus and primary Sjögren's syndrome in Scandinavian samples. Issue 6 (30th January 2012) - Bolstad, Anne Isine; Le Hellard, Stephanie; Kristjansdottir, Gudlaug; Vasaitis, Lilian; Kvarnström, Marika; Sjöwall, Christopher; Johnsen, Svein Joar Auglænd; Eriksson, Per; Omdal, Roald; Brun, Johan G; Wahren-Herlenius, Marie; Theander, Elke; et al.
Abstract : Objectives: Lymphotoxin β ( LTB ) has been found to be upregulated in salivary glands of patients with primary Sjögren's syndrome (pSS). An animal model of pSS also showed ablation of the lymphoid organisation and a marked improvement in salivary gland function on blocking the LTB receptor pathway. This study aimed to investigate whether single-nucleotide polymorphisms (SNP) in the lymphotoxin α ( LTA)/LTB/ tumour necrosis factor ( TNF ) gene clusters are associated with pSS. Methods: 527 pSS patients and 532 controls participated in the study, all of Caucasian origin from Sweden and Norway. 14 SNP markers were genotyped and after quality control filtering, 12 SNP were analysed for their association with pSS using single marker and haplotype tests, and corrected by permutation testing. Results: Nine markers showed significant association with pSS at the p=0.05 level. Markers rs1800629 and rs909253 showed the strongest genotype association (p=1.64E-11 and p=4.42E-08, respectively, after correcting for sex and country of origin). When the analysis was conditioned for the effect of rs1800629, only the association with rs909253 remained nominally significant (p=0.027). In haplotype analyses the strongest effect was observed for the haplotype rs909253G_rs1800629A (p=9.14E-17). The associations were mainly due to anti-Ro/SSA and anti-La/SSB antibody-positive pSS. Conclusions: A strong association was found between several SNP in the LTA/LTB/TNF α locus and pSS, some of which led to amino acid changes. These data suggest a role for this locus in the development of pSS. Further studies are needed to examine if the genetic effect described here is independent of the known genetic association between HLA and pSS.